PROBLEME MAJORE ALE CADRELOR DIDACTICE DIN ROMÂNIA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2007)
The paper identified the dimensions for changing the teacher’s role in a society of knowing, characterized by a higher level of social links and a more active implication of the citizens, as well as the requested competences for the teachers to answer efficiently to such a change; it also analysed the change dimensions of the teacher’s role, stressing the changes in their duties and the problems they have to face with; it presented the factors that caused these changes.